Physiological control of growth, reproduction and lactation in deer - Ryg, Morten (Rangifer, 1986)
The physiological mechanisms controlling the growth, lactation and reproductive cycles of cervids, and the control of allocation of energy to different organs are discussed. The growth cycle may be secondary to an appetite cycle, regulated by changes in the secretion of prolactin, gonadal steroids, and possibly unknown factors. The reproductive cycle is controlled by changes in the release at the hypothalamic hormone GnRH, and by changes in the feedback effect of gonadal steroids. These cycles are probably the result of the timing effects of nutrition and changing photoperiod on an endogenous, circannual rhythm. The effect of photopenod is mediated by the pineal hormone melatonin. The physiological mechanisms controlling the partitioning of substrates between milk production, fetal growth and the tissues of the mother are poorly understood, but may involve changes in the secretion of growth hormone, insulin and triiodothyronine.